EVALUASI ANTIOKSIDAN DAN MUTU KIMIA COOKIES PEGAGAN (CENTELLA ASIATICA) DENGAN PEMANIS STEVIA (STEVIA REBAUDIANA) - Kintan Nuryantini; Dewi Amrih (Universitas Muhammadiyah Semarang, 2026)
Centella asiatica (pegagan) is a medicinal plant known to have high potential as a natural antioxidant source. The utilization of pegagan in the development of functional foods can be achieved by incorporating pegagan leaf powder into snack products such as cookies. In addition, innovation in cookie formulation can be carried out by substituting conventional sugar with natural sweeteners such as stevia (Stevia rebaudiana), which has low caloric value and is considered safe for diabetic consumers. This study aimed to determine the effect of the addition of pegagan leaf powder and stevia sweetener substitution on the antioxidant activity and chemical quality of cookies. The study employed a factorial Completely Randomized Design (CRD) with variations in the concentration of pegagan leaf powder and stevia sweetener in the cookie formulation. The parameters analyzed included antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, reducing sugar content using Nelson-Somogyi method, and moisture content using thermogavimetry method. The results showed that the addition of pegagan leaf powder and stevia sweetener significantly affected the reducing sugar content and moisture content of cookies, but had no significant effect on antioxidant activity. These findings indicate that the incorporation of pegagan leaf powder and stevia sweetener can influence the chemical characteristics of cookies and has potential for the development of functional cookie products.